2017
DOI: 10.1136/archdischild-2016-311245
|View full text |Cite
|
Sign up to set email alerts
|

Does painless rectal bleeding equate to a colonic polyp?

Abstract: We confirm that the most common symptom of rectal polyps is painless rectal bleeding. However, only one in five patients with this clinical history has a rectal polyp at endoscopy. The polyp pickup rate at endoscopy is greater (28%) when a history of both rectal bleeding and mucous per rectumispresent. This information can be used to counsel parents preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
4
1
Order By: Relevance
“…Multiple studies have reported that juvenile polyps were more common in male patients [3,4,7,13]. Our study, however, did not demonstrate a statistically significant difference between male and female patients.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Multiple studies have reported that juvenile polyps were more common in male patients [3,4,7,13]. Our study, however, did not demonstrate a statistically significant difference between male and female patients.…”
Section: Discussioncontrasting
confidence: 89%
“…Three of them had proctitis. This rate is lower than that reported in a recent study that analyzed patients with painless rectal bleeding with or without abdominal pain but with no change in bowel movements, in which inflammatory bowel disease was present in 10.7% of the patients [13].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In our study, the most common cause of isolated hematochezia was colorectal polyps (27.6%), which are in line with previous studies of 19.5–44.1%. 1 11 13 However, unlike previous studies we were also capable of identifying a relatively high proportion of patients with anal fissures (14.2%). Although, anal fissures can be observed by inspection and a history of constipation, there are uncertain cases in which the fissures are located in the anal canal or cases of an insufficient physical exam owing to the unwillingness of the child to cooperate.…”
Section: Discussionmentioning
confidence: 59%
“…Colonic polyps are quite common in children, which are always isolated and benign. Painless lower gastrointestinal bleeding represents the most common presentation of colonic polyps in children [ 1 , 2 ]. Intussusception mainly occurs during infancy and early childhood.…”
Section: Introductionmentioning
confidence: 99%